2012
DOI: 10.1021/ol300209s
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstituted Piperidines via Iodolactonization: Application to the Asymmetric Synthesis of (+)-Pseudodistomin D

Abstract: Conjugate addition of lithium (S)-N-allyl-N-(α-methyl-p-methoxybenzyl)amide to methyl (E,E)-hepta-2,5-dienoate furnished the corresponding β-amino ester. N-Protecting group manipulation, ring-closing metathesis, and ester hydrolysis gave enantiopure [N(1')-tert-butoxycarbonyl-1,2,3,6-tetrahydropyridin-2'-yl]ethanoic acid. Subsequent iodolactonization gave a bicyclic iodolactone scaffold. This key intermediate was elaborated to (+)-pseudodistomin D [in >99% ee and 7% yield over 16 steps from methyl (E,E)-hepta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The PMB group in 13 was deprotected with DDQ to obtain the primary alcohol 15 , which upon oxidation with TEMPO/BAIB in a mixture of CH 2 Cl 2 /H 2 O (2 : 1), furnished compound 16 in 83% yield over two steps. Iodolactonization of the acid 16 with I 2 and NaHCO 3 in acetonitrile followed by deiodination of 17 under Barton‐McCombie conditions afforded bicyclic lactone 11 in 86% yield (two steps). The olefin in compound 11 was oxidatively cleaved under Jin's one‐pot protocol using OsO 4 , 2,6‐lutidine, and NaIO 4 to obtain the aldehyde intermediate 9 in 83% yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The PMB group in 13 was deprotected with DDQ to obtain the primary alcohol 15 , which upon oxidation with TEMPO/BAIB in a mixture of CH 2 Cl 2 /H 2 O (2 : 1), furnished compound 16 in 83% yield over two steps. Iodolactonization of the acid 16 with I 2 and NaHCO 3 in acetonitrile followed by deiodination of 17 under Barton‐McCombie conditions afforded bicyclic lactone 11 in 86% yield (two steps). The olefin in compound 11 was oxidatively cleaved under Jin's one‐pot protocol using OsO 4 , 2,6‐lutidine, and NaIO 4 to obtain the aldehyde intermediate 9 in 83% yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to eradicate the competing dehydration pathway (and, hence, formation of TsNH2), the possibility of effecting olefination of the aldehyde functionality prior to isocyanate trapping and cyclic carbamate formation was considered. Although reaction of 11 with Ph3P=CH(CH2)3OBn has already been shown to result in olefination and epoxide formation (undesired in this case), 14 and 20 but also that the formal substitution of the iodide functionality by an amino func-tionality had proceeded with inversion of configuration, as required for the synthesis of pseudodistomin E. With this transformation (i.e., 7 to 19) established, an end-game for the elaboration of lactone 7 into pseudodistomin E using the decarboxylative coupling of a carboxylic acid and a dialkylzinc reagent, recently reported by Baran et al, 23 E,8'Z):(6'Z,8'E):(Z,Z) ratio], the oxazolidinone moiety within 31 was cleaved using KOH in hot MeOH to give 32, and finally the N-Boc group was removed from 32 using HCl in hot MeOH to give synthetic pseudodistomin E 33 in 72% yield (from 31) and 82:8:8:2 dr [(E,E):(6'E,8'Z):(6'Z,8'E):(Z,Z) ratio]. The integrity of the diene geometry is clearly somewhat compromised during the coupling reaction, but the deprotection steps occur without further isomerization.…”
mentioning
confidence: 95%
“…3,4 Together, they represent one of the rare examples of the isolation of alkaloids from sea creatures. Unsurprisingly, there has been interest in the development of syntheses of members of this family of alkaloids in both racemic and enantiopure form, with routes to pseudodistomins A, 5 B, [5][6][7][8][9] C, [10][11][12] D, 13,14 and F 7 having been reported to date. These endeavors have enabled not only the structures of the alkaloids to be confirmed (in fact, the structures of pseudodistomins A and B originally proposed by Kobayashi et al 15 were revealed to be erroneous and were thus revised), 6,16,17 but also their absolute configurations.…”
mentioning
confidence: 99%
See 2 more Smart Citations